Additions to the Flora of Nizamabad District, Andhra Pradesh, India - Dinesh, Vijigiri; Sharma, P. P. (Indian Forester, 2012)
During botanical explorations of Nizamabad district between 2007 to 2011, a total 20 plant species of angiosperms belonging to 15 families have been reported for the first time, which are listed over with detailed information.